The effects of intrauterine insemination and single embryo transfer or modified natural cycle in vitro fertilization on offspring's health—Follow-up of a randomized clinical trial. (November 2019) - Mintjens, S.; Menting, M.D.; Gemke, R.J.B.J.; van Poppel, M.N.M.; van Wely, M.; Bensdorp, A.J.; Tjon Kon Fat, R.I.; Mol, B.W.J.; Painter, R.C.; van de Beek, C.; Roseboom, T.J.
Abstract: Objective: Does ovarian hyperstimulation and/or the in vitro procedure of assisted reproduction affect neurodevelopmental and physical health of the offspring? Study design: Infertile couples were randomly allocated to intrauterine insemination with controlled ovarian hyperstimulation (IUI-COH), modified natural cycle in vitro fertilization (IVF-MNC) or single embryo transfer IVF (IVF-SET). We compared neurodevelopmental and physical health in childhood (4–7 years). We used age-appropriate questionnaires to assess behavioral problems (Child Behavior Check List (CBCL)) and executive functioning (Behavior Rating Inventory of Executive Function (BRIEF)). We measured body mass index Z-score, waist- and hip-circumference, body fat percentage, blood pressure Z-scores, pulse wave velocity, glucose, insulin, insulin resistance, total cholesterol, high- and low-density lipoprotein cholesterol, triglycerides, and high sensitivity c-reactive protein. We compared groups by analysis of variance. Results: We examined 191 (57%) of the 333 children born in the study at a mean age of 5.5 years (range 4.0–7.6 years). We found no statistically significant differences between randomization groups in children's neurodevelopmental or physical health indices (all p -values > 0.05). Comparing the outcomes between actual method of conception, including a naturally conceived group, also did not show statistically significant differences. Conclusions: Although this follow-up study was not powered on childhood outcomes and limited power due to attrition may have hampered detection of subtle effects, we found no indications of differences in neurodevelopmental and physical health between ovarian hyperstimulation and/or the in vitro procedure of assisted reproduction. Future trials should be powered on child outcomes, and aim to optimize follow-up rates to provide answers that are more definitive.